PENGARUH PEMBERIAN PUPUK MAJEMUK NPK TERHADAP PERTUMBUHAN BIBIT Gyrinops versteegii - Dina Juanita; Marthen T. Lasut; Josephus I. Kalangi; Josea Singgano (COCOS, 2013)
ABSTRACTThis research aims to analyze the effect of NPK compound fertilizer and a good dose of growth of seedlings Gyrinops versteegii..This study used a Randomized Complete design of experiment method (RAL), with 5 treatment da 4 replicates. Treatment that is given that (A) no fertilizer (control), (B) NPK fertilizer plant 0.5 grams/Compection, (C) compaction NPK fertilizer 1 g/plant, (D) NPK fertilizer plant 1.5 grams/Compection, (E) Compection NPK fertilizer 2 grams/plant. The planting medium used in this research is tanaah, da sand with a ratio of 2: 1. The observed variables are height-diameter seedlings, seeds, leaves and large amount of leaves.The research results showed that NPK compound fertilizer on seedling Compection Gyrinops versteegii real influence only on stem diameter. (B) treatment of 0.5 grams/plant and treatment (C) 1 gram/plant gives good results on stem diameter growth of plants. While on a high number of seedlings, leaf area and leaf gave no real influence.